2015
DOI: 10.1016/j.nmni.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel strain of Shigella dysenteriae serotype 7 from India

Abstract: We describe a strain of Shigella dysenteriae serotype 7 which had novel biochemical and genetic characters. Unlike other S. dysenteriae, it produced gas, fermented mannitol, was a late-lactose fermenter and harboured the set 1A and set 1B genes. The significance of such atypical strains is that they are difficult to identify. If such strains are missed, they could prove to be a serious public health problem because the infectious dose is very low and they may harbour integrons contributing to drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…During the study period, S . flexneri remained the most dominant serogroup, as documented earlier [ 16 , 17 ]. The closest serogroup following this was the S .…”
Section: Discussionsupporting
confidence: 60%
“…During the study period, S . flexneri remained the most dominant serogroup, as documented earlier [ 16 , 17 ]. The closest serogroup following this was the S .…”
Section: Discussionsupporting
confidence: 60%
“…During the study period, S. flexneri remained the dominant (112/187=60 %) serogroup, as documented in earlier studies from our centre and other studies as well. The closest serogroup (60/187=32 %) following this was S. sonnei, which showed a steep rise in the study period (2012-2017) compared to previously documented results from our centre (2008-2011) [19][20][21]. Few other studies have also reported on the rising dominance of S. sonnei closely following S. flexneri.…”
Section: Discussionsupporting
confidence: 68%
“…Reports of Atypical serotypes of S.flexneri are available from various parts of the world like Korea, Russia, Bangladesh and China [3][4][5][6][7]. Similarly, novel serovars of S.dysentriae have been reported from Bangladesh and Puducherry [8,9]. These were proven to harbour multiple virulence factors on their invasion plasmids and chromosomes.…”
Section: Case Reportmentioning
confidence: 99%